Pola Hidup Manusia Baru dalam Kristus Menurut Efesus 4:17-30 - pangaribuan, ipan morris pangaribuan (Sekolah Tinggi Teologia Kerusso Indonesia, 2023)
AbstractAccording to the Bible, life outside of Christ is the old life, Col.3:29. This new human lifestyle isvery important for every believer to have so that he becomes a different person from the previousone and becomes a renewed person. The pattern of life prepares humans to have eternal life.Indicators of a new human life pattern in Christ are; putting off the old man by leaving the old life,being renewed in Spirit and mind, or being in a position of spirit and mind having been renewed byGod, putting on the new man by leaving the things of the flesh (flesh), and Putting on the New manin Christ. Putting on the new man means living in the truth of God's Word and putting His Word intopractice. People with a new life will radiate through various behaviors such as; words that can becontrolled, don't become angry, working hard, and becoming a person who doesn't grieve the HolySpirit. In the discussion, using qualitative methods, namely literature or literature studies